Gestão da inovação : o caso do Grupo Tramontina S.A. - Ranghetti, Carolina Dal Ponte (My University, 2017)
The aim of this work was to verify how is the innovation management in three companies Tramontina Group SA sought to also carry out a comparative of each company's Innovation Management studied with the three innovation management models covered in the theoretical framework: Model Stage-Gate Cooper; Model Hopper Clark and Wheelwright and Development; Model Tidd routines, Bessant and Pavitt. With this qualitative exploratory study of multiple cases held ten semi-structured interviews. The interpretation of the data was in the form of discourse analysis with the assistance Atlas.ti software version 6. The results show that each unit of Tramontina has its administrative structure and its way to the Innovation Management. The converging factors among all studied units are the two schedules, PLANES and PAIM. As a result of the comparative Innovation Management model units with innovation management models of literature we can point out that all units have similar and different factors with each model, concluding that any company purely a practice models, but a compound of the characteristics of both methods.
O objetivo desta dissertação foi verificar como é feita a Gestão da Inovação em três empresas do Grupo Tramontina S.A. Buscou-se também realizar um comparativo da Gestão da Inovação de cada empresa estudada com os três modelos de Gestão da Inovação abordados no referencial teórico: modelo Stage-Gate de Cooper; modelo Funil do Desenvolvimento de Clark e Wheelwright e; modelo de Rotinas de Tidd, Bessant e Pavitt. Com caráter qualitativo esta pesquisa exploratória de múltiplos-casos realizou dez entrevistas semiestruturadas. A interpretação dos dados ocorreu na forma de análise de discurso com a assistência do software Atlas.ti Versão 6. Os resultados mostram que cada unidade da Tramontina possui sua estrutura administrativa bem como sua forma de fazer a Gestão da Inovação. Os fatores convergentes entre todas as unidades estudas são os dois planejamentos, PLANES e PAIM. Como resultado ao comparativo do modelo de Gestão da Inovação das unidades com os modelos de Gestão da Inovação da literatura pode-se apontar que todas as unidades possuem fatores semelhantes e diferentes com cada um dos modelos, concluindo que nenhuma empresa pratica puramente um dos modelos, mas sim um composto de características de ambos os métodos.
Keywords: Administração de empresas; Inovações tecnológicas - Administração; Desenvolvimento organizacional; Industrial management; Technological innovations - Management; Organizational change